Molecular phylogenetics of the superfamily Stromboidea (Caenogastropoda): New insights from increased taxon sampling - Irwin, Alison R.; Bouchet, Philippe; Crame, J. Alistair; Harper, Elizabeth M.; Kronenberg, Gijs C.; Strong, Ellen E.; Williams, Suzanne T. (Zoologica scripta, 2024)
The superfamily Stromboidea is a clade of morphologically distinctive gastropods which include the iconic Strombidae, or ‘true conchs’. In this study, we present the most taxonomically extensive phylogeny of the superfamily to date, using fossil calibrations to produce a chronogram and extant geographical distributions to reconstruct ancestral ranges. From these results, we confirm the monophyly of all stromboidean families; however, six genera are not monophyletic using current generic assignments (Strombidae: Lentigo, Canarium, Dolomena, Doxander; Xenophoridae: Onustus, Xenophora). Within Strombidae, analyses resolve an Indo‐West Pacific (IWP) clade sister to an East Pacific/Atlantic clade, together sister to a second, larger IWP clade. Our results also indicate two pulses of strombid diversification within the Miocene, and a Tethyan/IWP origin for Strombidae—both supported by the fossil record. However, conflicts between divergence time estimates and the fossil record warrant further exploration. Species delimitation analyses using the COI barcoding gene support several taxonomic changes. We synonymise Euprotomus aurora with Euprotomus bulla, Strombus alatus with Strombus pugilis, Dolomena abbotti with Dolomena labiosa, and Dolomena operosa with Dolomena vittata. We identified cryptic species complexes within Terebellum terebellum, Lambis lambis, “Canarium” wilsonorum, Dolomena turturella and Maculastrombus mutabilis. We reinstate Rimellopsis laurenti as a species (previously synonymised with R. powisii) and recognise Harpago chiragra rugosus and Lambis truncata sowerbyi valid at the rank of species. Finally, we establish several new combinations to render Lentigo, Dolomena, and Canarium monophyletic: Lentigo thersites, Dolomena robusta, Dolomena epidromis, Dolomena turturella, Dolomena taeniata, Dolomena vanikorensis, D. vittata, “Canarium” wilsonorum, Hawaiistrombus scalariformis, Maculastrombus mutabilis, Maculastrombus microurceus.